Electrical control of 180° domain walls in an antiferromagnet - O. J. Amin; S. Reimers; F. Maccherozzi; S. S. Dhesi; V. Novák; R. P. Campion; K. W. Edmonds; P. Wadley (APL Materials, 2023)
We demonstrate the reversible current-induced motion of 180° antiferromagnetic domain walls in a CuMnAs device. By controlling the magnitude and direction of the current pulse, the position of a domain wall can be switched between three distinct pinning sites. The domain wall motion is attributed to a field-like spin–orbit torque that induces the same sense of rotation on each magnetic sublattice, owing to the crystal symmetry of CuMnAs. Domain wall motion is observed for current densities down to ≈2.5×1010 A/m2 at room temperature.